A proposed human resource management model for zakat institutions in Malaysia - Hasan, Aznan; Hassan, Rusni; Engku Ali, Engku Rabiah Adawiah; Engku Ali, Engku Muhammad Tajuddin; Abduh, Muhamad; Noordin, Nazrul Hazizi (Emerald Publishing Limited, 2019)
Purpose The purpose of this study is to propose a contemporary human resource management (HRM) framework by zakat institutions, which collect and manage religious alms, both obligatory (zakat) and voluntary (ṣadaqah), in Malaysia.